ALTERED SUPER ENHANCER – PROMOTER INTERACTIONS MEDIATED BY YY1 UNDERLIE AGE-INDUCED TRANSCRIPTOME. (20th December 2022) - Dang, Weiwei; Sun, Luyang; McCauley, Brenna
Abstract: Significant changes in transcriptome during aging have been observed in various tissues and cell types, even at the single-cell level. However, the molecular mechanisms that underlie these changes remain poorly understood. Using an ex vivo mesenchymal stem cells (MSC) replicative aging model and Hi-C technology, we discovered that, rather than large-scale changes in chromosome conformation, alterations to super enhancer – promoter looping interactions had the best positive correlation with age-associated transcriptome. Furthermore, we found evidence that these age-induced transcriptomic changes are mediated by YY1, a key regulator of promoter-enhancer looping. This work, for the first time, unveiled a molecular mechanism elucidating the changes in transcription during aging.